Avaliação da soroprevalência do Parvovírus B19 em mulheres em idade fértil no município de Goiânia - Rios, Washington Luiz Ferreira (2008)
The goal of this study was to evaluate the prevalence of specific IgG antibodies against PB19 virus, which identify previous immunity, and IgM antibodies, characteristic of acute infection, in women of childbearing age in Goiânia, a capital city in the Midwestern Region of Brazil. To achieve this, 101 serum samples collected from health women identified via prenatal care services, birth control groups, communitarian work groups, and public night schools near Public Health Units were tested. The samples were stored in the section of Parasitology of the Tropical Pathology and Public Health Institute of the Federal University of Goiás (IPTSP/UFG) and were tested using ELISA (IgM and IgG) against parvovirus B19. The women were evaluated according to several aspects (economic, social, cultural, age, marital status, previous blood transfusion, pregnancy evolution, among others). The statistical tests used were variance analysis,  2 , and multivariance analysis (logistic regression). The results showed that the population analyzed was young, poor, presented low level of formal education, underwent regular prenatal care exams (in terms of number of attendances), and lived in brick houses with few rooms and many inhabitants, with a regular sanitation system. Prevalence of previous PB19 infection was the lowest found in the literature available (8.9%), average prevalence detected was 60%, and acute infection was 26.7%, similar to the one found in periods of epidemics. Furthermore, 25% of the acutely infected women were pregnant during the sample collection, which represented a risk of vertical transmission.